A Modified Delphi Survey on the Signs and Symptoms of Low Back Pain: Indicators for an Interventional Management Approach. Issue 1 (9th December 2013) - Cid, José; De La Calle, José L.; López, Esther; Del Pozo, Cristina; Perucho, Alfredo; Acedo, María Soledad; Bedmar, Dolores; Benito, Javier; De Andrés, Javier; Díaz, Susana; García, Juan Antonio; Gómez‐Caro, Leticia; et al.
Abstract Background Low back pain (LBP) symptoms and signs are nonspecific. If required, diagnostic blocks may find the source of pain, but indicators of suspect diagnosis must be defined to identify anatomical targets. Objective To reach a consensus from an expert panel on the indicators for the most common causes of LBP. Material and Methods A 3‐round (2 telematic and 1 face‐to‐face) modified Delphi survey with a questionnaire on 78 evidence‐based indicators of 7 LBP etiologies was completed by 23 experts. Results 98.7% of the questionnaire was consensuated. The most accepted indicators were for zygapophysial joint pain, painful ipsilateral paravertebral palpation, worsening with trunk extension, paravertebral musculature spasm on the affected articulation, and referred pain above the knee, without radicular pattern. For sacroiliac joint pain, unilateral pain when seating, with at least 3 described provoking tests: Approximation; gapping; Patrick's; Gaenslen's; thigh thrust; Fortin finger; and Gillet's tests. For discogenic pain, midline pain that may be provoked by pressure on the spinal processes at the affected level; for quadratus lumborum muscle, painful palpation on both the L1 level paravertebral region, referred to iliac crest, and the iliac crest, referred to greater trochanter. For iliopsoas muscle, pain elicited by thigh flexion, referred to buttock, inguinal region, and anterior thigh. For pyramidal muscle, pain while sitting on the affected side and positive Freiberg's test. For radicular pain, paresthesias and positive Lassègue's test at 60°. Conclusion Seventy‐seven diagnostic suspect indicators of LBP conditions were consensuated. These may facilitate conservative or interventional pain management decision‐making.